Determinants of women’s empowerment in the context of sustained adoption of improved crop varieties in rural Eastern Uganda - Sanya, Losira Nasirumbi; Kyazze, Florence Birungi; Lutomia, Cosmas Kweyu; Mukhwami, Johnworker Toywa; Kakuru, Medard; Shimali, Fred; Nchanji, Eileen Bogweh (BioMed Central, 2025)
Women play an important role in agricultural production worldwide, and their empowerment in agriculture remains crucialto the sector’s growth. Recently, both governmental and nongovernmental organizations have undertaken interventions, including thepromotion of several agricultural technologies, aimed at empowering women to attain desired development goals. Empowerment isexpected to enable women to participate in household decisions and enhance their ability to invest in and sustain the use of improved cropvarieties. Despite the interventions, there is limited evidence on the determinants of women’s empowerment concerning the sustaineduse of improved seeds. This study aimed to investigate determinants of women’s empowerment in the context of sustained use ofimproved seed varieties among Ugandan smallholder women. Methods: The study applied a quantitative research method that enhancedunderstanding of gender relations within the selected household. During the intra-household survey, a total of 298 men and women from149 households, who were the principal decision makers in the same household, were interviewed. Findings: We find that disparities inaccess and sustained use of improved crop varieties still exist among women and men; perceptions and patterns of decision making varywith an observed mismatch between actual and perceived empowerment in decision making; and men still dominate decision makingpower which impacts sustained use. Women’s self-assessed level of their own decision making power was significantly lower than men’sassessment of women’s decision making power in a household. Descriptive results revealed a positive association between sustaineduse of improved varieties and women empowerment. Regression results indicated a strong positive influence of age, group membership,number of farming training, and participation in off-farm employment on women’s self-reported level of involvement in decision making.The age of the woman, joint ownership of land, and number of improved crops planted significantly influenced men’s perceptions ofwomen’s empowerment level. Conclusions and recommendations: We conclude that women’s empowerment in decision making haspotential to contribute to closing the gender gap in sustained use. This illuminates the need to be more intentional about women’sparticipation, decision making and agency in development interventions if we are to achieve greater impact in sustained use of agriculturaltechnologies and better livelihoods. Ultimately, this calls for transformative programs that tackle the negative influence of social norms thatlimit women from participating in household decision making. Educational programs should be targeted at challenging traditional genderroles and biases to encourage actual involvement of women in household decision making.